2020
DOI: 10.22495/cbv16i2art3
|View full text |Cite
|
Sign up to set email alerts
|

Board structure, firm performance and risk: Recent evidence from Greece

Abstract: This paper examines the relationship between the characteristics of the board and the performance and risk of a firm using data from forty-five Greek listed companies over the period 2015-2018. The analysis considers various alternative performance measures, both accounting-based and stock-based, as well as two measures for risk. The board characteristics considered are the size of the board, the number of female members on the board, the number of non-executive members on the board, and the duality re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…While this sample only represents about a half of the initial firms' population, this sample size is still larger relative to existing studies that examined non-financial (ESG) performance and board gender diversity in Greece (e.g. Karaiskos et al, 2019;Rompotis, 2020;Skouloudis et al, 2014;Terjesen et al, 2016). Bloomberg started to report firms' ESG scores and board of director data since 2006.…”
Section: Sample Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…While this sample only represents about a half of the initial firms' population, this sample size is still larger relative to existing studies that examined non-financial (ESG) performance and board gender diversity in Greece (e.g. Karaiskos et al, 2019;Rompotis, 2020;Skouloudis et al, 2014;Terjesen et al, 2016). Bloomberg started to report firms' ESG scores and board of director data since 2006.…”
Section: Sample Formationmentioning
confidence: 99%
“…Research studies have identified that companies from some EU countries, such as Norway and Germany, have been considered as early adopters of the EU Directive 2014/95/EU, especially to increase women participations (gender quota) in corporate leadership, while others, such as Greece and Cyprus, have been considered as later adopters (Terjesen et al, 2015(Terjesen et al, , 2016Xhaho et al, 2021). This study focuses on Greece since Greece has been considered as one of the lagging countries to implement policies that promote gender diversity in corporate leadership within the European Union (Rompotis, 2020). Extant literature has examined the development of corporate governance and corporate social responsibility in Greece (e.g.…”
Section: Introductionmentioning
confidence: 99%